2022
DOI: 10.1177/00220345221123256
|View full text |Cite
|
Sign up to set email alerts
|

TRAF3IP2–IL-17 Axis Strengthens the Gingival Defense against Pathogens

Abstract: Recent genome-wide association studies have suggested novel risk loci associated with periodontitis, which is initiated by dysbiosis in subgingival plaque and leads to destruction of teeth-supporting structures. One such genetic locus was the tumor necrosis factor receptor–associated factor 3 interacting protein 2 ( TRAF3IP2), a gene encoding the gate-keeping interleukin (IL)–17 receptor adaptor. In this study, we first determined that carriers of the lead exonic variant rs13190932 within the TRAF3IP2 locus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In periodontal disease, studies observed that Casp11 deficiency led to an elevated bacterial load of P.g or F. nucleatum in gingival tissue (Almeida-da-Silva et al 2019; De Andrade et al 2021). Another study also reported alterations in microbiota due to deletion of an inflammation-related gene Traf3ip2 in PD (Zhang, Sun, et al 2023). In favor of previous reports, our study revealed alterations in the composition of the subgingival microbiota with Casp11 -/- mice compared with WT mice.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In periodontal disease, studies observed that Casp11 deficiency led to an elevated bacterial load of P.g or F. nucleatum in gingival tissue (Almeida-da-Silva et al 2019; De Andrade et al 2021). Another study also reported alterations in microbiota due to deletion of an inflammation-related gene Traf3ip2 in PD (Zhang, Sun, et al 2023). In favor of previous reports, our study revealed alterations in the composition of the subgingival microbiota with Casp11 -/- mice compared with WT mice.…”
Section: Discussionmentioning
confidence: 90%
“…For example, it has been found that recruitment of leukocytes was involved, in which Caspase-11 influences the abundance of P.g (Almeida-da-Silva et al 2019). The IL-17–TRAF3IP2 pathway was also found to be a regulator of oral plaque composition, subsequently influencing alveolar bone loss (Zhang, Sun, et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a common chronic inflammatory disease caused by microbial infection in the susceptible hosts and it has been documented that IL-17 plays both protective and destructive roles in the progression of periodontitis [ 37 , 38 ]. Some studies have found that IL-17 dominated the inflammatory network associated with periodontitis traits [ 39 , 40 ] ( Table 1 ), which indicated that abnormal inflammatory responses induced by IL-17 may cause tissue damage. One potential mechanism is that IL-17 is able to amplify inflammation through excessive neutrophil recruitment by enhancing proinflammatory cytokine/chemokine production, which results in further osteoclast activation and bone resorption [ 41 ].…”
Section: Immunopathogenesis Of Il-17mentioning
confidence: 99%
“…Homeostatic IL-17-TRAF3IP2-neutrophil axis underpinning host defense against a keystone periodontal pathogen. [39,40] Encephalomyelitis IL-17-mediated positive feedback loop of IL-6 signaling through NF-κB and STAT3 contributes to enhanced autoimmune encephalomyelitis. [47] Virus associated inflammation Bone marrow-derived IL-17A is required for the development of pneumonitis.…”
Section: Immunopathogenesis Of Il-17mentioning
confidence: 99%